PENGARUH KEPEMIMPINAN, KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP EMPLOYEE ENGAGEMENT (KETERIKATAN KARYAWAN) (Studi Kasus PT. BPR Lengayang, Pesisir Selatan) - ., Syabrina; ., Maivalinda (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2024)
This research is a quantitative research. This study aims to determine the influence of leadership, organizational culture, and compensation on employee engagement. The object of research is PT BPR Lengayang. The total population in this study This study is 41 employees who work at PT. BPR Lengayang. The sampling technique used is purposive sampling technique. Purposive criteria sampling criteria used are all permanent employees who work at BPR Lengayang except leaders and non-permanent employees. The sample in this study were 35 permanent employees of PT BPR Lengayang. Data collection techniques were carried out through questionnaires, interviews and observation. The results showed that the leadership variable had an insignificant effect on employee engagement, compensation variables have a significant effect on employee engagement, and organizational culture variables have a significant effect on employee engagement. employees, and organizational culture variables have a significant effect on employee engagement.